DILEMMAS STORIES LEARNING MODEL IN INDONESIAN LANGUAGE LEARNING TO IMPROVE STUDENTS' SCIENTIFIC WRITING SKILLS - Yuliarti; Yatin Mulyono ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2023)
This study aimed to evaluate the Indonesian language learning process in terms of the scientific writing abilities of senior high school students and find solutions to these learning problems. This type of research is a mixed method. Samples were obtained randomly from three senior high schools in Indonesia with 272 students as subjects. The process of gathering data involved watching teaching aids. Observing the learning process and evaluating the students' scientific writing skills utilizing instrument assessments that have been Aiken formula verified and concept validated using Confirmatory Factor Analysis (CFA) with the Linear Structural Model (Lisrel). Observational data on curricular papers and learning process observations are reported descriptively. Comparatively, statistics on learning outcomes in the form of students' writing skills are examined by estimating the proportion of pupils who fulfill traditionally established standards. The results showed that the students' scientific writing skills needed to meet the classical achievements. The evaluation results showed that a new, more effective learning strategy was required to improve students' scientific writing skills by developing learning models. Developing the inquiry learning model of local wisdom dilemmas stories (ILWDS) is recommended as an alternative to making learning effective and efficient.